Istinbath Method in Strengthening Ultra Qui Judicial Principles in Judicial Decisions - Suwitno Yutye Imran; Apripari Apripari; Ade Sathya Sanathana Ishwara; Erifendi Churniawan; Aristama Mega Jaya; Nurikah Nurikah (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
the method of Istinbath is necessary to support the principle of Ultra Qui Judicat, enabling judges to possess moral characteristics in considering not only knowledge and reason but also Islamic law when making legal decisions. Overall, the significance of the Istinbath method in supporting the principle of Ultra Qui Judicat is paramount, especially in addressing contemporary and empirical issues not governed by legislative regulations. The aim of this research are : explain the concept of Istinbath and Ultra Qui Judicat influence the judge's decisions and the application of the Istinbath method used to reinforce the principle of Ultra Qui Judicat to judicial decisions. The result shows that The method of Istinbath is closely related to the principle of Ultra Qui Judicat since both share the same objective of achieving justice. In practice, judges can use the method of Istinbath to interpret the law and apply the principle of Ultra Qui Judicat in criminal cases. The principle of Ultra Qui Judicat and the method of Istinbath are essential instruments for judges in the criminal justice system to achieve justice in decision-making